SAT0268 Tocilizumab Therapy in Children with Polyarthicular Course Juvenile Idiopathic Arthritis. (15th July 2016) - Alexeeva, E.; Denisova, R.; Valieva, S.; Bzarova, T.; Isayeva, K.; Sleptsova, T.; Chistyakova, E.; Chomahidze, A.; Lomakina, O.; Soloshenko, M.; Fetisova, A.; Kashchenko, E.
Abstract : Background: Patients with polyarticular-course Juvenile idiopathic arthritis (pcJIA) have risk for profound disability.Although these patients may respond to methotrexate (MTX) or biological agents approved for pcJIA, up to 30% continue to have active disease.Interleukin-6 (IL-6) is concentrations are positively correlated with the severity of joint involvement and with C-reactive protein (CRP) levels. Tocilizumab is effective drug for the treatment of JIA refractory to immunosuppressive drugs. Objectives: To evaluate safety and efficacy of tocilizumab treatment in children with pcJIA Methods: Analysis of efficacy and safety tocilizumab therapy was performed in 46 patients (4 - RF+, 3-enthesitis related arthritis, 1-psoriatic JIA) and in 24 patients, whom follow up period was 6 and 12 m. Median age was 9, 8 y (range; 1, 9 to 17, 2 y) and median disease duration was 5, 1y (range; 0.4 to 13, 7 y). Tocilizumab was administrated intravenously at a dose of 8or 10 mg/kg every 4 weeks. 29 patients were treated by biologics previously. The majority of patients received concomitantDMARDs, 31 patients received methotrexate, 1-leflunomid, 1-sulfasalazin, 5-cyclosporin and 8- prednisolone at dose 0.4 (0.2; 1) mg/kg/day. 14 patients had uveitis: 6-not active, 1-subactive and 7-active. Efficacy end points included the American College of Rheumatology (ACR)for improvement 30 (ACR30), ACR50, ACR70, ACR90 and criteria of inactive disease andindex JADAS10. During the follow-up period, significant side-effects were sought. Results: The ACR Pedi 30, 50, 70, 90 and 100 improvement were achieved by 92% (n=36), 82% (n=32), 56% (n=22), 23% (n=9), and 12% (n=5) of patients at Week 24 (n=39), by 100% (n=24), 87% (n=21), 83% (n=20), 54% (n=13), and 20% (n=5) of patients at Week 48 (n=24)respectively. Inactive disease was achieved by 14/39 (36%) of patients at week 24 and by 12/24 (50%) of patients at week 48. The JADAS10 decreased from 23, 4 (14, 8; 27, 8) to 6, 2 (1, 6; 11, 8) at week 24 (p<0.001) and to 2, 0 (0, 5; 4, 9) at week 48 (p<0.001). The number of platelets decreased from 383 x109/l (302; 488) to 250 (220; 282) at week 24 (p<0.001) and to 258 (216; 284) at week 48 (p<0.001), number of leucocytes – from 8, 8 x109/l (7, 6; 9, 9) to 6, 5 (5, 3; 7, 3) at week 24 (p<0.001) and to 6, 4 (4, 7; 6, 8)) at week 48 (p<0.001); level of hemoglobin increased from 112 (100; 123) g/l to 126 (118; 132) at week 24 (p<0.01) and to 129 (122; 136)) at week 48 (p<0.001).The frequently observed non-severe adverse events were nasopharyngitis, upper respiratory tract infections and gastroenteritis. No cases of opportunistic infections, malignancies or death were reported. 12 patients had incidences of neutropenia, 2 – thrombocytopenia, 7-increased level of ALT and AST. Tocilizumab treatment was discontinued in 7 patients during the follow-up 48 weeks period. The causes for cancellation were lack of efficacy (n=6), infusion reaction (n=1), flare (n=1). 5patients were switched to antiTNF blockers and 2 – to abatacept. Conclusions: Tocilizumab treatment provided clinically meaningful improvement for patients with pcJIA. Tocilizumab induced remission of the disease The safety profile of tocilizumab was consistent that seen in other studies Disclosure of Interest: E. Alexeeva Grant/research support from: Roche, Novartis, UCB, R. Denisova Grant/research support from: Roche, Novartis, Pfizer, UCB, S. Valieva Grant/research support from: Roche, T. Bzarova Grant/research support from: Pfizer, K. Isayeva Grant/research support from: Roche, Novartis, T. Sleptsova Grant/research support from: Novartis, UCB, E. Chistyakova: None declared, A. Chomahidze: None declared, O. Lomakina: None declared, M. Soloshenko: None declared, A. Fetisova: None declared, E. Kashchenko: None declared